Serviço Social e Saúde Mental- Reflexões sobre competências e atribuições privativas de assistentes sociais - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present article was proposed as Residency Completion Work (TCR), based on living as a resident of the Social Work with the Multiprofessional Integrated Residency Program in Health - Emphasis on Collective Mental Health, Federal University of Pampa - Unipampa (RS). The objective of this study is to reflect on the materialization of the Privilege Competencies and Privileges of Social Work professionals in the field of Mental Health, in order to assess the professional practice of social workers with the Public Policy of Mental Health. For that, a research with mixed focus, of an exploratory nature, was carried out from bibliographical sources. The technique of content analysis was employed, just as the method used was the dialectical-critical one. For this, a mapping of Social Service production in the subject of Mental Health was carried out in journals of scientific recognition in the field of knowledge of Social Service, relating to the Privileges' Competencies and Private Assignments. Mental health is a field with great challenges, but also of immense potential both in professional practice and in scientific production.
Social service and mental health - reflectionson competences and privative assignments of social assistants
Keywords: Social Worker; Mental Health; Professional Competence; Private Assignments; Serviço Social; Saúde Mental; Competências Profissionais; Atribuições Privativas; Saúde mental coletiva; CNPQ::CIENCIAS DA SAUDE